2020
DOI: 10.1177/1535370220915826
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction of ovarian aging using ovarian expression of BMP15, GDF9, and C-KIT

Abstract: This study investigated ovarian expressions of bone morphogenetic protein 15 (BMP15), growth differentiation factor 9 (GDF9), and C-KIT according to age in female mice to determine whether these factors can be served as new potential biomarkers of ovarian aging. Ovaries were collected from mice aged 10, 20, 30, and 40 weeks, and ovarian expressions of BMP15, GDF9, and C-KIT were examined by real-time PCR, Western blot, and immunohistochemistry. Follicle counts were measured on histological hematoxylin and eosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Some authors reported that the hormonal production of granulosa cells during folliculogenesis was modulated by the oocyte, which would secrete an inhibitor of P 4 , according to the stage of follicular development (El-Fouly et al, 1970;Vanderhyden & Macdonald, 1998). The oocyte-secreted signalling factors induce the expression of the genes associated with cumulus cells' differentiation and mitosis, in a paracrine way (Alam et al, 2018), such as GDF9 and BMP15 (Paulini & Melo, 2011), which could also serve as new potential biomarkers of ovarian ageing in mice (Park et al, 2020). The results of the current study demonstrated that the overexpression of these factors exerts an influence on the luteinization of bovine GCs cultured in vitro in a homologous system, and in an autocrine way, in agreement with the results of Li et al (2000).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported that the hormonal production of granulosa cells during folliculogenesis was modulated by the oocyte, which would secrete an inhibitor of P 4 , according to the stage of follicular development (El-Fouly et al, 1970;Vanderhyden & Macdonald, 1998). The oocyte-secreted signalling factors induce the expression of the genes associated with cumulus cells' differentiation and mitosis, in a paracrine way (Alam et al, 2018), such as GDF9 and BMP15 (Paulini & Melo, 2011), which could also serve as new potential biomarkers of ovarian ageing in mice (Park et al, 2020). The results of the current study demonstrated that the overexpression of these factors exerts an influence on the luteinization of bovine GCs cultured in vitro in a homologous system, and in an autocrine way, in agreement with the results of Li et al (2000).…”
Section: Discussionmentioning
confidence: 99%
“…BMP15, GDF9, and c-KIT play critical roles in folliculogenesis through interaction between oocytes and cumulus cells (Gilchrist et al, 2008). Ovarian expressions of BMP15, GDF9, and c-KIT decrease with age (Park et al, 2020), and their expression levels in cumulus granulosa cells could serve as potential biomarkers of ovarian aging and predicting oocyte developmental potential (Li et al, 2014).…”
Section: Biomarkers Of Ovarian Agingmentioning
confidence: 99%
“…GDF9, signaling through the SMAD signaling pathway, upregulates the TZP-associated genes fascin homolog 1 (Fscn1), an actin bundling protein and myosin X (Myo10), an actin-based motor protein, both known to induce formation of filopodia (Bohil et al, 2006;Hashimoto et al, 2011;El-Hayek et al, 2018;Baena and Terasaki, 2019). With age, oocyte GDF9 expression declines (Li et al, 2014;Park et al, 2020;Gong et al, 2021) along with the expression of Fscn1 and Myo10, and the numbers of TZPs are reduced by approximately 40%, resulting in a marked decrease in gap junctional communication between the oocyte and the granulosa cells (El-Hayek et al, 2018).…”
Section: Bi-directional Communication Role For Gap Junctions In Follicular Metabolismmentioning
confidence: 99%